Análisis de los estados financieros y propuestas de mejora a la Cooperativa de Ahorro y Crédito “Cristo Rey” de la Ciudad de Loja periodo 2014 – 2015 - Contento Ruiz, Juliana Alexandra (2016)
This thesis called: “ANALYSIS TO THE FINANCIAL STATEMENTS AND PROPOSALS FOR IMPROVEMENT TO credit union "CHRIST THE KING" OF THE CITY OF LOJA Period 2014-2015” was developed in order to comply with the overall objective to assess the situation economic and financial entity and thus help correct decision making. To this was complied with the objectives set beginning with a vertical and horizontal analysis to periods of study subjects, then apply indicators according to the PEARLS monitoring and thereby make proposals for improvement to achieve adequate profitability and an efficient administrative and financial management of the institution. The methodology used came from the collected information provided by the accounting department, then different methods of financial analysis and vertical analysis which could determine the degree of incidence of the accounts clearly identifying that loan portfolio was applied was the most representative this is due to the granting of loans by the company to improve the quality of life of its members, also the horizontal analysis was performed to identify the variations from one year to another with their respective causes and the application of indicators according to the PEARLS Monitoring same as were performed taking into account the goal of each ratio, they determined that the financial institution has high delinquency by loan portfolio, in terms of liquidity the bank remains at a medium level and profitability for the current year had a decrease, for this improvement proposals which are designed to provide possible solutions to the shortcomings noted was raised. It follows that there is high delinquency portfolio credit and low profitability so that managers are advised to run this financial analysis as this addressed to improve the financial situation of the cooperative and thus help managers that make appropriate decisions to help the institutional growth.